2013
DOI: 10.5858/arpa.2012-0605-oa
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Immunohistochemical Scoring for Epidermal Growth Factor Receptor Expression in Non–Small Cell Lung Cancer: Round Robin Test

Abstract: Context.-The addition of cetuximab to first-line chemotherapy substantially prolonged survival in patients with advanced non-small cell lung cancer whose tumors expressed high levels of epidermal growth factor receptor (EGFR; immunohistochemistry score of !200 on a scale of 0-300).Objective.-To evaluate the interobserver reproducibility of this EGFR immunohistochemistry scoring system, based on both the tumor cell membrane staining intensity (graded 0-3þ) and the percentage of cells staining at each intensity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…In the present study, a good interobserver agreement of 80-90% was observed with a mean coefficient of 0.983 among three pathologists, and the positivity in the samples was 70%, which is consistent with other studies (28,30). In the present study, a better concordance for the H-scores was observed when using a cut-off of 100 (73.4-83.4%); meanwhile, the concordance of the cut-off of 200 ranged from 67.5-77.3%.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the present study, a good interobserver agreement of 80-90% was observed with a mean coefficient of 0.983 among three pathologists, and the positivity in the samples was 70%, which is consistent with other studies (28,30). In the present study, a better concordance for the H-scores was observed when using a cut-off of 100 (73.4-83.4%); meanwhile, the concordance of the cut-off of 200 ranged from 67.5-77.3%.…”
Section: Discussionsupporting
confidence: 79%
“…Regarding the reproducibility of the H-score, Rüschoff et al (28) evaluated the interobserver reproducibility of this EGFR IHC scoring system. A high agreement was observed amongst the scores with an overall concordance rate of 90.9% and a mean coefficient of 0.812 (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Similar issues with reproducibility were reported in solid malignancies for HER2 expression in breast cancer 13 and for EGFR in lung carcinoma. 14 The studies mentioned above for various markers in DLBCL, and on HER2 and EGFR in carcinomas, focused on analyzing protein markers expressed by tumor cells. In contrast, immunohistochemical studies in FL mostly report on densities and distribution patterns of non-malignant immune cell populations present in the microenvironment.…”
mentioning
confidence: 99%